2020
DOI: 10.1038/s41598-020-62188-4
|View full text |Cite
|
Sign up to set email alerts
|

Sea-level rise exponentially increases coastal flood frequency

Abstract: Sea-level rise will radically redefine the coastline of the 21 st century. For many coastal regions, projections of global sea-level rise by the year 2100 (e.g., 0.5-2 meters) are comparable in magnitude to today's extreme but short-lived increases in water level due to storms. Thus, the 21 st century will see significant changes to coastal flooding regimes (where present-day, extreme-but-rare events become common), which poses a major risk to the safety and sustainability of coastal communities worldwide. So … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(143 citation statements)
references
References 50 publications
3
138
0
2
Order By: Relevance
“…A key application of this analysis is the ability to estimate emergence times, the first year when coastal inundation will occur at a specific frequency (e.g., weekly, daily, and 100 days per year). This assists in further relating projections to impacts and provides insights into tipping points and the exponential nature of SLR impacts (Taherkhani et al, 2020). Emergence times are intended to be a tool for policymakers and impacts scientists to help contextualize the increasingly frequent coastal inundation that is expected in the next 80 years.…”
Section: Implications For Adaptation—emergence Times Aris Emission mentioning
confidence: 99%
“…A key application of this analysis is the ability to estimate emergence times, the first year when coastal inundation will occur at a specific frequency (e.g., weekly, daily, and 100 days per year). This assists in further relating projections to impacts and provides insights into tipping points and the exponential nature of SLR impacts (Taherkhani et al, 2020). Emergence times are intended to be a tool for policymakers and impacts scientists to help contextualize the increasingly frequent coastal inundation that is expected in the next 80 years.…”
Section: Implications For Adaptation—emergence Times Aris Emission mentioning
confidence: 99%
“…High water levels are caused by the interaction between these two patterns, which mostly occur in July-October. Additionally, Ridder et al (2018) found that the majority of these types of compound events are accompanied by the presence of an atmospheric river over the Netherlands.…”
Section: Data and Study Areamentioning
confidence: 99%
“…The impact function is designed to reproduce W L max given a set of predictors (see Section 3.2). We explored different approaches, including multiple linear regression (MLR), random forests (RF) (Meinshausen, 2006) and artificial neural networks with stochastic gradient descent for regression (NN) (He et al, 2015;Phan, 2015). The different regression models are evaluated by means of the root-mean-square error (RMSE), the mean absolute error (MAE), the linear (Pearson's) correlation coefficient r and the error associated to return level estimates.…”
Section: Impact Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis for assessing contemporary coastal (ocean) flood risk depends upon local extreme sea level (ESL) probabilities from TGs ( Figure 1A) to map associated exposure (Kulp and Strauss, 2019) as shown in Figure 1B. Future estimates typically include localized RSL projections (e.g., Hunter, 2012;Tebaldi et al, 2012;Church et al, 2013;Kopp et al, 2014;Sweet and Park, 2014;Buchanan et al, 2017;Wahl et al, 2017;Ghanbari et al, 2019;Oppenheimer et al, 2019;Frederikse et al, 2020;Taherkhani et al, 2020). Most of these studies use the 100-year ESL (1% annual chance level) as a suitable flood threshold to assess impacts and communicate risk, though empirically derived height thresholds for flooding of various severities is preferable as to align with actual infrastructure vulnerabilities and weather warnings affecting daily decision making (Sweet and Park, 2014;Sweet et al, 2018).…”
Section: Introductionmentioning
confidence: 99%